Strategi Citra Living With Aesthetic And Quality Reviewer Pada Platform Tiktok Live Natasha Surya - Kartika Cahya Jauhariya; Meithiana Indrasari Yunus; Eko Pamuji (DIGICOM : Jurnal Komunikasi dan Media, 2022)
Natasha Surya or commonly called Kak Nat is an influencer who has pursued the world of social media in 2017, especially on Tiktok social media. Natasha Surya is one of the influencers who has managed to get the verified badge or blue tick from Tiktok. This sign means that Tiktok has confirmed Kak Natasha's account as an account that is already well-known in its field. This influencer who built his image as a living with an aesthetic and quality reviewer has a special strategy to be trusted by many parties as the most effective marketing party on social media, especially Tiktok. Researchers have a goal so that the wider community understands and understands the right marketing strategies on Tiktok Live, especially the strategies used by Kak Nat. Choosing a qualitative descriptive research method will dissect in detail the findings or results obtained by the researcher. Using the theory of image formation from John S Nimpoeno which explains that the image has a process that will produce results in the form of attitudes, opinions, responses, and even certain behaviors. Therefore, researchers feel that image formation is very important in marketing activities. As a result, many unexpected new discoveries such as the selection of a brand that wants to work with the influencer greatly affect the formation of his image. A teaser video before holding a live stream is one way to increase the number of viewers during the live stream.